Role of milk and honey in the tolerance of lactobacilli to oxidative stress - Castro, Vanessa Moraes Ramalho (Braz J Microbiol, 2021)
In the development of functional probiotic food, the carrier matrices should be carefully selected and optimized to ensure the highest levels of probiotic survival in the symbiotic food along storage. Because milk and honey food matrices are rich in antioxidant substances, the aim of the research was to evaluate their effect in protecting lactobacilli from reactive oxygen species (ROS) generated by the addition of hydrogen peroxide. Viability assays were performed with and without the addition of H(2)O(2), in three different matrices: 0.9% peptone saline, 5% honey, or 12% reconstituted skim milk. The milk matrix provided protection for the Lacticaseibacillus paracasei DTA83 and Lacticaseibacillus rhamnosus DTA76. However, this protective effect was not observed in the survival of Lactobacillus acidophilus La 5. Honey solution did not maintain the viability of probiotic microorganisms exposed to hydrogen peroxide and, on the contrary, caused a significant reduction in the population of L. rhamnosus DTA76 (p < 0.001). Lower membrane lipid peroxidation due to H(2)O(2) exposure was observed in L. acidophilus La 5 and L. rhamnosus DTA76, but this marker showed no relation with viability. It was concluded: (i) lactobacilli from the Lacticaseibacillus genus were the ones that benefited most from the lactic environment; (ii) the absence of the protective effect of honey was possibly due to the presence of Fe(2+) which reacts with H(2)O(2) to produce hydroxyl radicals; and (iii) cell viability did not correlate with membrane lipid peroxidation, and it is not a good marker to evaluate this type of damage in cells of different microorganisms.